2008
DOI: 10.1128/aac.01487-07
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Population Structure of Streptococcus pneumoniae Isolates in Spain Carrying mef and mef plus erm (B)

Abstract: Macrolide resistance among Streptococcus pneumoniae clinical isolates has risen to prominence. The rate of resistance to macrolides is even higher than that to penicillin, particularly in Spain and some other European countries, such as France, Poland, Greece, and Portugal (17, 23). In most European countries, erythromycin resistance is mainly due to the presence of the erm(B) gene. This gene encodes an rRNA methylase responsible for the macrolide-lincosamide-streptogramin B resistance (MLS B ) phenotype and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
1
11
0
2
Order By: Relevance
“…The presence of known genetic resistance determinants was verified in all erythromycin-resistant isolates: ermTR was confirmed to be responsible for the iMLS phenotype (Varaldo et al, 2009); the coexistence of two erm alleles (ermB/ ermTR) was found in 5.6 % of all MLS isolates, although only one was phenotypically expressed, as reported previously in streptococcal and pneumococcal isolates (Cascone et al, 2002;de la Pedrosa et al, 2008;Giovanetti et al, 2012;Silva-Costa et al, 2008). In our study, certain emm types were specifically recovered among erythromycin-resistant isolates, and were associated with different phenotypes: emm75, emm2 and emm4 with an M phenotype and emm77 with an iMLS phenotype.…”
Section: Discussionmentioning
confidence: 50%
“…The presence of known genetic resistance determinants was verified in all erythromycin-resistant isolates: ermTR was confirmed to be responsible for the iMLS phenotype (Varaldo et al, 2009); the coexistence of two erm alleles (ermB/ ermTR) was found in 5.6 % of all MLS isolates, although only one was phenotypically expressed, as reported previously in streptococcal and pneumococcal isolates (Cascone et al, 2002;de la Pedrosa et al, 2008;Giovanetti et al, 2012;Silva-Costa et al, 2008). In our study, certain emm types were specifically recovered among erythromycin-resistant isolates, and were associated with different phenotypes: emm75, emm2 and emm4 with an M phenotype and emm77 with an iMLS phenotype.…”
Section: Discussionmentioning
confidence: 50%
“…Chromosomal DNA was isolated using a standardised procedure (DNeasy Blood & Tissue Kit; QIAGEN, Hilden, Germany). The distinction between mef(A) and mef(E) was made using a multiplex PCR [20] with the following primers: mefAF, 5 -AATACAACAATTGGATT-3 ; mefEF, 5 -AAGGAGTTGTGGTTCTGA-3 ; and mefR, 5 -CCAATGATTTACACCGATT-3 . The PCR mixture for 25 L contained 15 mM Tris-HCl, 50 mM KCl (pH 8.0), 25 mM MgCl 2 , 100 M of each nucleotide, 0.15 mM of mefAF and mefEF primer and 0.25 mM of the mefR primer plus 1.5 U of AmpliTaq Gold ® DNA Polymerase (Applied Biosystems, Darmstadt, Germany).…”
Section: Dna Isolation and Detection Of Macrolide Resistance Genes Bymentioning
confidence: 99%
“…However, to our knowledge, this is the first report of resistance to levofloxacin in strains belonging to this clone. In addition, it is noteworthy that we have detected resistance to fluoroquinolones among usually antibiotic-susceptible clones circulating in Spain: Netherlands 7F -ST191, ST1201 (19A), and ST2639 (10A) (1,6,19).…”
Section: Among 1349mentioning
confidence: 99%